Click Chemistry ‐ Inspired Synthesis of Porphyrin Hybrid Glycodendrimers as Fluorescent Sensor for Cu(II) Ions. Issue 28 (22nd July 2022) - Agrahari, Anand K.; Kumar, Sunil; Pandey, Mrituanjay D.; Rajkhowa, Sanchayita; Jaiswal, Manoj K.; Tiwari, Vinod K.
Abstract: An expeditious and modular CuAAC 'click' protocol has been exploited for the construction of porphyrin cored hybrid glycodendrimers of G1 and G2 generation. The developed porphyrin hybrid glycodendrimers were characterized using extensive spectral analysis including NMR ( 1 H, 13 C, and 19 F), MS, MALDI‐TOF, IR, and SEC datas and evaluated for their sensing ability for a range of metal ions, where they displayed notable sensing for Cu(II) ion with solvatochromism properties. Abstract : A modular CuAAC 'click' protocol has been exploited for the construction of porphyrin cored hybrid glycodendrimers of G1 and G2 generation. The developed glycodendrimers were well characterized and evaluated for their sensing ability for a range of metal ions, where they displayed notable sensing for Cu(II) ion with solvatochromism properties.